Measuring Spiritual Integrity in Turkish Culture: A Psychometric Approach to Understanding the Relationship Between Spirituality and Well-Being - Okan, Nesrullah; Eksi, Fusun; Zengin, Erdal; Eksi, Halil (Springer, 2025)
This study examines the validity and reliability of the Spiritual Integrity Scale (SIS), a tool developed to assess the alignment between individuals' spiritual values, beliefs, and behaviours. The study adopted a three-phase scale development approach, consisting of exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and criterion validity and reliability assessments.The findings indicated that the SIS exhibits a single-factor structure with strong validity and reliability. The item loadings ranged from 0.63 to 0.83, explaining 54.99% of the total variance, while the Kaiser-Meyer-Olkin (KMO) value was 0.945 and Bartlett's Test (p < 0.001) confirmed the data's suitability for factor analysis. The CFA results demonstrated an adequate model fit (chi(2)/df = 2.897, RMSEA = 0.0, SRMR = 0.031).The Cronbach's Alpha reliability coefficient was 0.947, and the test-retest correlation was 0.84, indicating strong internal consistency and stability over time. Criterion validity was assessed using the Spiritual Psychological Robustness Scale, revealing a significant positive correlation (r = 0.448, p < 0.001), suggesting that higher spiritual integrity is associated with greater psychological resilience and well-being. These findings underscore the pivotal role of spiritual integrity in cultivating mental fortitude and existential stability. The SIS provides a validated tool for measuring spiritual alignment, offering practical applications for clinicians, counsellors and researchers seeking to explore the influence of spirituality on psychological well-being and personal growth. Furthermore, the scale's strong psychometric properties establish it as a reliable instrument for evaluating spirituality's role in mental resilience, guiding interventions aimed at enhancing holistic well-being. This study makes a significant contribution to the expanding body of literature on spirituality and psychological health, reinforcing the importance of spiritual integrity in fostering emotional balance, life satisfaction, and overall psychological resilience.
Keywords: Spiritual integrity; Psychometric validation; Reliability and validity; Moral values and alignment; Turkish culture